2019
DOI: 10.1158/1078-0432.ccr-19-0189
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Metabolic Profiling Predicts Sensitivity of High MYC-Expressing Atypical Teratoid/Rhabdoid Tumors to Glutamine Inhibition with 6-Diazo-5-Oxo-L-Norleucine

Abstract: Purpose: Atypical teratoid/rhabdoid tumors (AT/RT) are aggressive infantile brain tumors with poor survival. Recent advancements have highlighted significant molecular heterogeneity in AT/RT with an aggressive subgroup featuring overexpression of the MYC proto-oncogene. We perform the first comprehensive metabolic profiling of patient-derived AT/RT cell lines to identify therapeutic susceptibilities in high MYCexpressing AT/RT.Experimental Design: Metabolites were extracted from AT/RT cell lines and separated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
(85 reference statements)
1
14
0
Order By: Relevance
“…S2). The results suggested that the regulatory mechanism of CBP in breast cancer mainly involves the induction of apoptosis, which is in line with some published studies 37,38 . Based on the compounds in RJSJ, we obtained 682 targets, 33 of which were also targets of CBP, including ve apoptosis-related genes (Fig.…”
Section: Analysis Of the Potential Synergistic Mechanism Of Rjsj And supporting
confidence: 90%
“…S2). The results suggested that the regulatory mechanism of CBP in breast cancer mainly involves the induction of apoptosis, which is in line with some published studies 37,38 . Based on the compounds in RJSJ, we obtained 682 targets, 33 of which were also targets of CBP, including ve apoptosis-related genes (Fig.…”
Section: Analysis Of the Potential Synergistic Mechanism Of Rjsj And supporting
confidence: 90%
“…6-diazo-5-oxo-L-norleucine (DON) and its naturally occurring prodrug azotomycin are diazo analogues of glutamine that irreversibly inhibit multiple glutamine-utilizing enzymes. GA have been observed to cause decreased proliferation or induction of apoptosis, depending on genetic context, cell/tissue type, and environment (16)(17)(18). GA have been tested clinically (19), including for sarcomas (20).…”
Section: Introductionmentioning
confidence: 99%
“…CHLA-02 might also have more embryonic phenotypes than CHLA-05 due to high NPM1 gene expression and AFP positivity. This could be due to a high expression of MYC and high glutamine consumption in CHLA-02 [ 67 ]. In breast cancer patients, MYC expression increased the risk of breast cancer brain metastasis [ 68 ].…”
Section: Discussionmentioning
confidence: 99%